A novel asymmetric amphiphilic porous film of (PLA)-(PLA-b-PEG)-(PEG) with controlled gradual pore size - Ran Huang; Boxin Zhou; Zhuping Nie; Weiwei Ding; Xilin Jiang; Yihu Song (Results in Materials, 2020)
A porous film of (PLA)-(PLA-b-PEG)-(PEG) is fabricated as a general biomedical device for potential applications. For the purpose of providing both mechanic strength and bio-friendly supporting, the film is designed to be asymmetric with a PLA-densed hydrophobic surface and a PEG-densed hydrophilic surface. Beyond the conventional technique to achieve amphiphilicity and porosity via simple blend of two typical biopolymers, a fine controlled processing is developed to achieve the gradual pore size along depth with the attendance of block polymer, which provides several advantages such as avoiding sharp phase separation, the gradual release of biofactors as a carrier, etc.